Analisis Faktor Keuangan terhadap Laba Bersih Perusahaan Consumer Non-Cyclicals di BEI - Saras Meilia Puspitasari (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Companies that have good performance can be shown when they generate profits for debt financing and capital owners. To achieve this direction, management must pay attention to sales and costs. This study aims to analyze working capital, sales, production costs, operating costs, and promotion costs against net income. The independent variables analyzed include working capital, sales, production costs, operating costs, and promotion costs, while the dependent variable is net income measured by profit before tax minus income tax expense. The results of the study indicate that working capital, sales, operating costs, and promotion costs have a significant effect on net income. Meanwhile, production costs do not affect profit.